Concurrent display of both alpha- and beta-turns in a model peptide - Srinivas, Deekonda; Vijayadas, Kuruppanthara N.; Gonnade, Rajesh G.; Phalgune, Usha D.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This article describes a model peptide that concurrently displays both alpha- and beta-turns, as demonstrated by structural investigations using single crystal X-ray crystallography and solution-state NMR studies. The motif reported herein has the potential for the design of novel conformationally ordered synthetic oligomers with structural architectures distinct from those classically observed.

Conformationally rigid aromatic amino acids as potential building blocks for abiotic foldamers - Ramesh, Veera V. E.; Roy, Arup; Vijayadas, Kuruppanthara N.; Kendhale, Amol M.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This communication describes the development of conformationally constrained unnatural aromatic amino acids, constructed on rigid backbone wherein the carboxyl and amino groups project in two dimensions (planes) on the aromatic framework. Such a feature offers the possibility of design and development of conformationally ordered synthetic oligomers with intriguing structural architectures distinct from those classically observed. Furthermore, such amino acids will have the potential to extend the conformational space available for foldamer design with diverse backbone conformation and structural architectures.

Unusual conformational similarity of two peptide folds featuring sulfonamide and carboxamide on the backbone - Vijayadas, Kuruppanthara N.; Davis, Hilda C.; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
Two folded peptides featuring carboxamide and sulfonamide at the core of the peptide fold have been shown to possess almost similar conformational features, despite the well-known fact that carboxamides and sulfonamides have strikingly different hydrogen-bonding and geometrical preferences.

Ant-pro reverse-turn motif. structural features and conformational characteristics - Thorat, Vijaykumar H.; Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Kale, Sangram S.; Ramesh, Veera V. E.; Davis, Hilda C.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; et al. (European Journal of Organic Chemistry, 2013)
This article details the characteristic conformational features of the Ant-Pro reverse turn ? a folded pseudo -turn motif that displays a closed nine-membered-ring hydrogen-bonded network involving just two amino acid residues, namely anthranilic acid (Ant; a constrained -amino acid), and proline (Pro; a constrained -amino acid). The results from the extensive investigation of ten crystal structures and their NMR conformations in the solution state provide a clear idea about the conformational characteristics of the Ant-Pro reverse turn. The Ant and Pro residues, which form the turn segment, maintain a perfect antiperiplanar orientation throughout, leaving little possibility for the formation of the otherwise possible six-membered hydrogen-bonding that requires a coplanar disposition of the two amino acid residues, as clearly evident from investigation of several crystal structures. The closed hydrogen-bonded network observed in the Ant-Pro reverse turn motif, formed in the forward direction of the sequence (12 amino acid interactions) involving only two amino acid residues, is in stark contrast to the native -turns that involve four residues to form hydrogen-bonded network featuring backward 14 amino acid interactions. The readily available two-residue Ant-Pro motif raises the possibility of a practical utility, particularly in the application of rigidifying flexible peptide backbones by inserting the robust Ant-Pro reverse turn motifs into their backbone.
Keywords: Peptides; Peptidomimetics; Protein folding; Protein structures

Ester vs. amide on folding: a case study with a 2-residue synthetic peptide - Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Gawade, Rupesh L.; Kotmale, Amol S.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2013)
Although known for their inferiority as hydrogen-bonding acceptors when compared to amides, esters are often found at the C-terminus of peptides and synthetic oligomers (foldamers), presumably due to the synthetic readiness with which they are obtained using protected peptide coupling, deploying amino acid esters at the C-terminus. When the H-bonding interactions deviate from regularity at the termini, peptide chains tend to ``fray apart''. However, the individual contributions of C-terminal esters in causing peptide chain end-fraying goes often unnoticed, particularly due to diverse competing effects emanating from large peptide chains. Herein, we describe a striking case of a comparison of the individual contributions of C-terminal ester vs. amide carbonyl as a H-bonding acceptor in the folding of a peptide. A simple two-residue peptide fold has been used as a testing case to demonstrate that amide carbonyl is far superior to ester carbonyl in promoting peptide folding, alienating end-fraying. This finding would have a bearing on the fundamental understanding of the individual contributions of stabilizing/destabilizing non-covalent interactions in peptide folding.

Switching the H-bonding network of a foldamer by modulating the backbone chirality and constitutional ratio of amino acids - Ramesh, Veera V. E.; Vijayadas, Kuruppanthara N.; Dhokale, Snehal A.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2013)
This communication describes the folding propensity of a hetero-foldamer motif featuring proline (Pro) and anthranilic acid (Ant) residues in a 1:2:1 (alpha: beta: alpha) constitutional ratio. Structural investigations unequivocally suggest that the hydrogen-bonding network of this foldamer motif can be switched between 9-membered and 6-membered by modulating the backbone chirality and constitutional ratio of the amino acid residues.

Heterogeneous foldamers from aliphatic-aromatic amino acid building blocks: current trends and future prospects - Nair, Roshna V.; Vijayadas, Kuruppanthara N.; Roy, Arup; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2014)
Chemists' constant pursuit of understanding of the underlying principles of nature's most intricate phenomenon such as protein folding has led to the development of the field of foldamers. The emergence of diverse classes of unnatural amino acid building blocks has unleashed countless opportunities to design, develop and explore the structural and functional aspects of synthetic peptides. One current trend in foldamer chemistry is the heterofoldamer approach, which involves systematic stoichiometric variation of various natural/unnatural amino acid residues, leading to conformational ordering with intriguing structural architectures. In this regard, the incorporation of aromatic amino acids provides efficient structural rigidification and tunability to the molecular scaffolds, which can exhibit a range of secondary structural features. Recent times have witnessed an upsurge of foldamers featuring aliphatic-aromatic residues with diverse structural propensities. This review is an effort to cover this rapidly developing field of foldamer science and also to envisage its future perspectives.
Keywords: Amino acids; Conformation analysis; Foldamers; hydrogen bonding; Peptides; Stacking interactions

Reversal of H-bonding direction by N-sulfonation in a synthetic reverse-turn peptide motif - Vijayadas, Kuruppanthara N.; Kotmale, Amol S.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Nair, Roshna V.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2015)
This communication depicts an intriguing example of hydrogen-bonding reversal upon introduction of a sulfonamide linkage at the N-terminus of a synthetic reverse-turn peptide motif. The ready availability of two sulfonyl oxygen atoms, as hydrogen-bonding acceptors, combined with the inherent twisted conformation of sulfonamides are seen to act as switches that engage/disengage the hydrogen-bond at the sticky ends/termini.

Disruption of native beta-turns: consequence of folding competition between native and orthanilic acid proline-based pseudo beta-turn - Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Chaitanya, K. N.; Kotmale, Amol S.; Gawade, Rupesh L.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2016)
Five tetrapeptides comprising beta-turn-forming elements and a pseudo beta-turn (C9 H-bonding) based on an SAntPro (orthanilic acid - proline) motif were designed and synthesized. Their extensive conformational investigation by single-crystal X-ray crystallography, solution-state 2D NMR spectroscopic, and nOe-restrained MD simulation studies revealed the formation of C14 or C9 folding and disruption of the native beta-turn (C10 H-bonding) architecture. The striking difference between the psi(psi(2)) angle of ``i + 2'' residues of native beta-turn and designed peptides suggest that formation of the native beta-turn is not favored. The results suggest that other turn-forming motifs can dramatically modulate the stability of the native beta-turn structure.
Keywords: Conformation analysis; hydrogen bonds; Peptidomimetics; structure elucidation

Residue dependent hydrogen-bonding preferences in orthanilic acid-based short peptide beta-turn motifs - Jedhe, Ganesh S.; Vijayadas, Kuruppanthara N.; Kotmale, Amol S.; Sangtani, Ekta; Shinde, Dinesh R.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (RSC Advances, 2016)
This communication describes the competition between native beta-turn (C10) and 2-aminobenzenesulfonic acid (SAnt)( orthanilic acid)-based pseudo beta-turn (C11) in their hybrid peptides. Solid-state crystal structure and solution-state NMR studies revealed that C10 and C11 can be simultaneously observed under appropriate conditions. The variable temperature NMR coefficient data suggest that the isolated C11/C14 hydrogen bond is weaker in comparison with the consecutive C10 and C11 turns.